Implementasi Visual Storytelling pada Animasi "Disconnected" - Azqi Az Zahra Khairun Nissa; Toto Sugito; Pandu Watu Alam (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
The growth of live streaming platforms has triggered behavioral changes among Generation Z audiences, such as fear of missing out (FOMO), poor sleep habits, and the normalization of toxic language. To visualize this situation, a 2D educational animation titled "Disconnected" was created by applying a visual storytelling approach. This approach utilizes three main components, namely symbols, composition, and setting, to convey the message regarding the phenomenon without utilizing verbal dialogue between characters. The creation process includes pre-production (research, interviews, script, storyboard), production (asset and animation creation using Adobe Illustrator and After Effects), and post-production (editing and rendering using Adobe Premiere Pro). This four-minute animation was published through the BLSDM Komdigi Bandung YouTube channel. Audience responses to the work were gathered through an online questionnaire involving 20 Gen Z respondents aged 14–29, using a Likert scale and open-ended essays. Results show that 95% of respondents found the animation easy to understand, while 85% found the message clearly conveyed through visuals and the storyline easy to follow. Essay data confirmed facial expressions, physical changes in characters, and symbolic elements such as speech bubbles as the elements that most helped audiences understand characters' psychological states. This study concludes that the application of symbol, composition, and setting components shows strong potential to effectively visualize behavioral changes of Gen Z audiences toward live streamers in educational animation.